Coherence scanning interferometry for additive manufacture - Gomez, Carlos; Thompson, Adam; DiSciacca, Jack; Lawes, Simon; Leach, Richard (2017)
Additive manufacture (AM) of metal components is a rapidly maturing technology; but given the large number of interrelated process parameters, it remains difficult to control to high precision. It has been observed that processing conditions may be associated with specific features in the surface texture [1], creating a drive to achieve fast, and reliable topographic measurement of metal AM surfaces. One of the most developed metal AM processes, selective laser melting (SLM), still produces parts that exhibit rough surface textures with dense distributions of features at a wide range of lateral and vertical scales, aspect ratios, and reflective properties; with the additional complication of the presence of high slopes, undercuts and surface recesses. These features make metal AM surfaces challenging to measure by both tactile and optical means [2,3].